Trends of water, sanitation, and hygiene (WASH) services and associated factors among households in Wolayita, Ethiopia: a cross-sectional study - Alemu, Z. A.; Girmay, A. M.; Collyer, B.; Kidane, A. W.; Weldegebriel, M. G.; Forbes, K.; Dinssa, D. A.; Adugna, E. A.; Kenea, M. A.; Mengistu, B.; Mehari, Z.; Tasew, G.; et al. (IWA Publishing, 2025)
This study aimed to assess the trends in water, sanitation, and hygiene (WASH) services over time and analyze associated factors influencing these services through a cross-sectional approach. The authors used a structured questionnaire to evaluate WASH indicators. They applied descriptive statistics for trend analysis and multivariate logistic regression analysis to identify associated factors. The findings revealed that basic drinking water services coverage in Arm 1 (WASH intervention area) increased by 238% or three times (from 8% in 2021 to 27% in 2023), while Arm 2 (WASH nonintervention) showed a 109% increase (from 11 to 23%) over the same period. Improved sanitation services were accessible to 8.6% of Arm 1 households (HHs) and 8.5% of Arm 2 HHs in 2023. Furthermore, awareness creation sessions on WASH practices conducted in the past 12 months were significantly correlated with WASH service improvements. The study indicated a slight improvement in basic drinking water service coverage; however, many HHs still lack adequate sanitation and hygiene facilities. Immediate action is necessary to achieve Sustainable Development Goal 6 regarding clean water and sanitation. Effective interventions should consider sociodemographic factors. Collaboration among government, NGOs, and communities is essential for sustainable WASH development in Ethiopia's Wolayita Zone and similar regions.